Extreme attributions predict transition from depression to mania orhypomania in bipolar disorder - Stange, J; Sylvia, L; Magalhães, P; Frank, E; Otto, M; Miklowitz, D; Berk, M; Nierenberg, A; Deckersbach, T (2013)
Background: Relatively little is known about psychological predictors of the onset of mania among individuals with bipolar disorder, particularly during episodes of depression. In the present study we investigated attributional style as a predictor of onset of hypomanic, manic or mixed episodes among bipolar adults receiving psychosocial treatment for depression. We hypothesized that "extreme" (i.e., excessively pessimistic or optimistic) attributions would predict a greater likelihood of developing an episode of mood elevation. Method: Outpatients with DSM-IV bipolar I or II disorder (N=105) enrolled in the Systematic Treatment Enhancement Program for Bipolar Disorder (STEP-BD) were randomly allocated to one of three types of intensive psychotherapy for depression or a brief psychoeducational intervention. Patients completed a measure of attributional style at baseline and were followed prospectively for up to one year. All analyses were by intent to treat. Results: Logistic regressions and Cox proportional hazards models indicated that extreme (both positively- and negatively-valenced) attributions predicted a higher likelihood of (and shorter time until) transition from depression to a (hypo)manic or mixed episode (ps<.04), independent of the effects of manic or depressive symptom severity at baseline. Extreme attributions were also retrospectively associated with more lifetime episodes of (hypo)mania and depression (ps<.05). Conclusions: Evaluating extreme attributions may help clinicians to identify patients who are at risk for experiencing a more severe course of bipolar illness, and who may benefit from treatments that introduce greater cognitive flexibility. © 2013 Elsevier Ltd.